Islamic Financial Literacy in Islamic Boarding Schools and Its Implications for the Preference of Islamic Financial Institutions - Wartoyo, Wartoyo; Yusuf, Ayus Ahmad; Kusumadewi, Rita (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
AbstractThis study aims to measure the level of financial literacy, analyze the influence of Islamic financial literacy levels on the preferences of Islamic financial institutions and estimate the impact of Islamic financial literacy among Islamic Boarding Schools on preferences and implications for Islamic Financial Institutions in Region III Cirebon. The method used is quantitative with mutinomial logistic regression analysis techniques. The data was collected using questionnaires from the population and the sample was among islamic boarding schools, both managers and students. The results of this study show that personal financial management literacy and Islamic economic literacy have an effect of 45% on Islamic banking preferences, 33% on sharia insurance preferences, and 29% on Islamic capital market preferences. This condition is in line with the results of measurements of Islamic financial literacy of islamic boarding school managers and students in the category of good literacy (well literate) in personal financial management and the category of sufficient literacy in the Islamic economy. The lowest is their literacy regarding sharia insurance of 25% and 29% (less literate) for the Islamic capital market. Keywords: Islamic Financial Literacy, Islamic Boarding Schools, Islamic Financial Institutions